Cognitive Restructuring in Group CBT Reduces Live-Streaming Addiction Among Indonesian Adolescents - Aminah Daulay; Neviyarni S (Yayasan Nurul Yakin Bunga Tanjung, 2025)
The pervasive rise of live-streaming video game platforms has triggered concerns about behavioral addiction among adolescents, particularly in rapidly digitalizing societies like Indonesia. This study examines the efficacy of group-based Cognitive Behavioral Therapy (CBT) in reducing live-streaming addiction symptoms among high school students. A quasi-experimental design with pre-test-post-test control group was implemented with 20 students (N=20) exhibiting moderate addiction levels, selected through purposive sampling. The experimental group (n=10) received five 45-minute sessions of manualized group CBT focusing on cognitive restructuring, while the control group (n=10) received standard group guidance. Results demonstrated significantly greater reduction in addiction scores for the experimental group (mean reduction=31 points, p=0.005) compared to controls (mean reduction=9 points, p=0.005), with large between-group effect size (p=0.000, r=0.65). Cognitive restructuring techniques effectively modified maladaptive thought patterns underlying compulsive viewing behaviors. The group modality enhanced treatment effectiveness through peer support and collective skill-building. These findings support the integration of evidence-based CBT protocols into school counseling services to address emerging behavioral addictions. Recommendations include counselor training in CBT techniques, development of culturally adapted interventions, and implementation of systematic screening for at-risk students. This study contributes to the growing literature on digital wellness interventions in educational contexts.